EFEK PEMBERIAN PUPUK BOKASHI DAN UREA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Solanum lycopersicum) - Uluputty, M. Riadh (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2015)
Tomato plants require intensive cultivation techniques to growth and high production. The use of fertilizers is one of the techniques that need to be developed. This study aimed to determine the effect of bokashi and urea fertilizer on the growth and production of tomato plants. The treatments tested is bokashi the dose of 0 or without bokashi, 10 ton Bokashi ha-1, and 20 ton bokashi ha-1, and urea that doses of 0 or without urea, 200 kg urea ha-1 and 400 kg urea ha-1. The study was designed using a randomized block design, two factors with three replications. The results showed that administration of bokashi fertilizer and urea together can cause interaction effects increased plant height, number of fruits per plant and fruit weight per plant, and a dose combination bokashi and urea best is 20 tons bokashi ha-1 and 400 kg urea ha-1.